A perda da visão como vivência de luto - Moura, Camila D'Avila (2019)
Visual disability is a phenomenon to which people are susceptible. Among others, factors such as aging can lead to this involvement. In Brazil, visual disability has grown, since it is derived from conditions such as vitamin A deficiency in the blood, or diseases such as diabetes. Severe accidents can also cause visual loss. Disability, in an important sense as vision, leads the person to reconfiguration of self-image, as well as to the restructuring of their social roles, resulting in a psychosocial transition similar to that of a person who loses a loved one. Recent studies emphasize that mourning is an expected reaction to several types of loss, giving mourning an oscillatory character, in which the mourner moves between being focused on the loss suffered, or on facing it. Such an understanding of the oscillatory character gives mourning peculiar characteristics to each mourning experience. When the mourning person is not given the right to express such singularities in his own way and in his own time, it runs the risk of making him go through an unrecognized mourning experience, which may be an additional suffering to that already experienced by the person who faces the pain of a stressful event. The objective of this study was to investigate the unrecognized mourning experienced in the experience of vision loss. The method used was the Clinical Case Study, deepening in the history of a person‟s life. Data collection was based on the transcription and thematic analysis of the participant's speech. After the loss of vision, a mourning experience was found, and it was possible to establish categories that helped to identify how factors such as prejudice and social stigma, environmental barriers and lack of understanding about visual disability contribute to the orientation towards loss. Factors such as family and social support, spirituality, rituals and the dynamics after the loss contribute to coping and restoration, identifying a mourning process reactive to the loss of vision, without a complicated mourning